Middle class pentecostalism in Argentina : inappropriate spirits - Köhrsen, Jens. (Religion in the Americas, 2016)
In Middle-Class Pentecostalism in Argentina: Inappropriate Spirits Jens Koehrsen offers an intriguing account of how the middle class relates to Latin America´s most vibrant religious movement. Based on pervasive field research, this study suggests that Pentecostalism stands in tension with the social imaginary of the middle class and is perceived as an inappropriate lower class practice. As such, middle class Pentecostals negotiate the appropriateness of their religious belonging by demonstrating distinctive tastes and styles of Pentecostalism. Abstaining from the expressiveness, emotionality, and strong spiritual practice that have marked the movement, they create a milder and socially more acceptable form of Pentecostalism. Increasingly turning into a middle class movement, this style has the potential to embody the future shape of Pentecostalism.